IMPLEMENTASI WAKAF BERJANGKA MENURUT UNDANG – UNDANG NOMOR 41 TAHUN 2004 DAN PERATURAN PEMERINTAH NO. 42 TAHUN 2006 - Salman Al Farisi (LPPM Universitas Pekalongan, 2022)
The understanding of the Indonesian people towards the understanding of waqf that cannot be separated from historical factors, people have adhered to it from ancient times until now. Waqf management institutions are very influential on the development of waqf in this nation in the history of Islamic civilization. Various waqf institutions have carried out waqf management for the community in accordance with the applicable laws and regulations. 41 of 2004 provides public confidence in waqf and provides public space so that they understand about waqf, especially term waqf according to Law no. 41 of 2004 concerning the implementation of waqf management. futures in Indonesia and its implementation which is also regulated in Government Regulation no. 42 of 2006. This term waqf is a manifestation of the development of the welfare of the people. The potential for developing waqf assets is very large, if managed productively, it can be a solution to welfare.